Treatment of adjuvant-induced arthritis with the combination of methotrexate and probiotic bacteria Escherichia coli O83 (Colinfant®) - Rovenský, Jozef; Stančíková, Mária; Švík, Karol; Utěšený, Jaroslav; Bauerová, Katarína; Jurčovičová, Jana (Folia microbiologica, 2009)
A certain relationship was observed between the gastrointestinal system, arthritis and immune system. Patients with rheumatoid arthritis have an altered microflora composition and disturbed intestinal defensive barrier. Effect of probiotic bacteria (Colinfant®; COL) with known favorable effect on intestinal microflora was determined on the methotrexate (MTX) treatment of adjuvant arthritis. Rats with adjuvant arthritis were administered methotrexate 0.5 mg/kg body mass 2-times weekly per os, COL 1 mL/kg body mass every second day per os, and a combination of MTX+COL for a period of 28 d from the immunization. Levels of serum albumin, body mass, changes in hind paw swelling, and arthrogram score were estimated in rats as variables of inflammation and destructive arthritis-associated changes. Treatment with MTX, as well as with the combination treatment with MTX+COL significantly inhibited both inflammation and destructive arthritis-associated changes. The combination treatment inhibited both the hind paw swelling and arthrogram score more remarkably than MTX alone; on the other hand, the difference between combination treatment and MTX alone was not significant. Treatment with COL alone had no effect on adjuvant arthritis in rats. Colinfant® can increase the preventive effect of MTX treatment in rat adjuvant arthritis by improving its antiarthritic effects.
Keywords: financování organizované; Animals; Probiotics; potkani inbrední LEW; kombinovaná terapie; Escherichia coli; lidé; Methotrexate; Financing, Organized; Male; Arthritis, Experimental; modely nemocí na zvířatech; Combined Modality Therapy; methotrexát; probiotika; Antirheumatic Agents; Disease Models, Animal; krysa rodu Rattus; zvířata; mužské pohlaví; antirevmatika; artritida experimentální; Rats, Inbred Lew; Rats; Humans